2012
DOI: 10.1002/polb.23073
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for controlling the active layer morphologies in OPVs

Abstract: This review focuses on the recent developments in our understanding of active layer morphologies for organic photovoltaic cells and approaches to obtain active layer morphologies for high power conversion efficiencies. The evolution of active layer morphologies, as studied by high resolution electron microscopy, X-ray and neutron scattering, and dynamic secondary ion mass spectrometry, is covered, along with strategies including the use of small molecule additives, polymer nanowires and polymer nanoparticles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 81 publications
1
35
0
Order By: Relevance
“…It needs to be taken into account that optimization of the morphology of the active layer is crucial to achieve the desired efficiency. An ideal morphology should be able to maximize interfacial interaction between the photoactive layer components in order to obtain higher exciton dissociation and also provide domain size within the order of the exciton diffusion length, crystalline domains to facilitate charge mobility and finally create percolated pathways to the electrodes [52,54].…”
Section: Challenges Of Organic Photovoltaicsmentioning
confidence: 99%
“…It needs to be taken into account that optimization of the morphology of the active layer is crucial to achieve the desired efficiency. An ideal morphology should be able to maximize interfacial interaction between the photoactive layer components in order to obtain higher exciton dissociation and also provide domain size within the order of the exciton diffusion length, crystalline domains to facilitate charge mobility and finally create percolated pathways to the electrodes [52,54].…”
Section: Challenges Of Organic Photovoltaicsmentioning
confidence: 99%
“…Also, the general expectation is that ordered structures such as the bicontinuous AlB 2 packing are required for applications such as OPVs ( Figure 11). 151,152 However, we have demonstrated that disordered structures can provide a bicontinuous structure with donor− acceptor interfaces for exciton splitting and efficient OPV devices. 68,208 Thermoelectric materials derived from polymers are another example that requires the assembly of multiple polymeric materials into specific morphologies.…”
Section: Impact On Functional Materialsmentioning
confidence: 99%
“…The improved performance was attributed to the removal of unwanted functional groups and the recovery of π-conjugated regions, thereby enhancing the conductivity of the graphene sheets and the charge-carrier mobility [50]. It has been reported that prolonged thermal annealing leads to the macrophase segregation of P3HT and PCBM domains and subsequently deteriorates the performance of the BHJ device by inhibiting charge generation [93]. In addition, the use of high temperatures ranging from 120 °C to 150 °C limits the application of some inexpensive plastic substrates.…”
Section: Effects Of Thermal and Solvent Annealing On The Active-layermentioning
confidence: 99%